Synthesis of Au-Cu Nano-Alloy from Monometallic Colloids by Simultaneous Pulsed Laser Targeting and Stirring - Ganjali, Mansoureh; Ganjali, Monireh; Khoby, Soraia; Meshkot, Mohammad Ali (Nano-Micro Letters, 2011)
Experimental work has been focused on the formation of alloyed Au-Cu nanoparticles under simultaneous laser exposure and mechanical stirring of mixed monometallic colloids, here referred to as dual procedure. As a feed for the dual procedure, Au and Cu monometallic nanoparticle colloids have been using a laser ablation technique. To accomplish this, bulk targets were ablated with 1064 nm wavelength Nd:YAG laser in a pure acetone (99.99%) environment. Ultraviolet-visible optical absorption spectrometry, transmission electron microscopy, X-ray diffraction and X-ray fluorescence technique have been used to characterize the nanoparticles. It has been found that experimental conditions such as stirring and laser parameters strongly affect the synthesized particle properties, including the size, shape, composition and stability of the nanoparticles. Alloy nanoparticles containing 39% Au - 61% Cu have also been prepared in the same process, but in two forms of a homogeneous alloy and a core-shell structure.